Large-scale sampling of the freshwater microbiome suggests pollution-driven ecosystem changes. (1st September 2022) - Premke, Katrin; Wurzbacher, Christian; Felsmann, Katja; Fabian, Jenny; Taube, Robert; Bodmer, Pascal; Attermeyer, Katrin; Nitzsche, Kai Nils; Schroer, Sibylle; Koschorreck, Matthias; Hübner, Eric; Mahmoudinejad, Termeh Hesam; et al.
Abstract: Freshwater microbes play a crucial role in the global carbon cycle. Anthropogenic stressors that lead to changes in these microbial communities are likely to have profound consequences for freshwater ecosystems. Using field data from the coordinated sampling of 617 lakes, ponds, rivers, and streams by citizen scientists, we observed linkages between microbial community composition, light and chemical pollution, and greenhouse gas concentration. All sampled water bodies were net emitters of CO2, with higher concentrations in running waters, and increasing concentrations at higher latitudes. Light pollution occurred at 75% of sites, was higher in urban areas and along rivers, and had a measurable effect on the microbial alpha diversity. Genetic elements suggestive of chemical stress and antimicrobial resistances ( IntI1, blaOX 58 ) were found in 85% of sites, and were also more prevalent in urban streams and rivers. Light pollution and CO2 were significantly related to microbial community composition, with CO2 inversely related to microbial phototrophy. Results of synchronous nationwide sampling indicate that pollution-driven alterations to the freshwater microbiome lead to changes in CO2 production in natural waters and highlight the vulnerability of running waters to anthropogenic stressors. Graphical abstract: Image 1 Highlights: Antibiotic resistant genes were nearly ubiquitous and in 85% of sampling sites. Freshwater microbial diversity is closely related to the amount of light pollution. The rivers were most impacted by light pollution and antibiotic resistance. CO2 was inversely related to microbial phototrophy. All freshwaters were CO2 net emitters, with higher concentrations in running waters.